Biological clock measures: assessing the association between the circadian and epigenetic clock as predictors of migration phenology and biological aging in wildlife - Le Clercq, Louis Stephanus (University of the Free State, 2024)
This thesis explores the use of biological clocks, studied at the molecular level, in understanding and predicting animal traits that change over time. In particular, the thesis focuses on two biological clocks: the circadian clock and the epigenetic clock. The study aimed to shed light on how these clocks, along with specific genes associated with them, influence traits such as migration patterns in birds and age in animals. In the investigation of circadian clock genes, this thesis presents a detailed review of existing literature, presenting both supporting and conflicting results on the association between clock gene polymorphisms and migration patterns. This review summarized the central hypotheses tested in these studies, identified several candidate genes that have been used, revealed distinct patterns in terms of the taxonomy and phylogeny of studied species, and present new insights into why conflicting results happen as well as what future research is needed. Furthermore, the review emphasizes the importance of considering molecular clock differences between lineages when studying multiple species. The two most studied candidate genes were then tested for associations to phenology in an intra-African migrant, the Diederik cuckoo, and provides the first evidence that phenotypic correlates identified in Eurasian passerine species is conserved for these species. The second part of the thesis delves into epigenetic clocks, examining two widely used methods: methylation and telomere length. A systematic review and meta-analysis were performed to compare the performance of these methods across vertebrate classes. Methylation was found to outperform telomere length in predictive power, with both methods showing promise as biomarkers for age determination in animals. To demonstrate the practical application of epigenetic clocks, the study included the development of a new age determination model on the African cheetah. Six candidate genes were identified, and a model using CpG methylation levels was created using machine learning techniques to refine the model, resulting in accurate age predictions. This approach offers a less invasive means of age estimation for population monitoring. The research also introduces two new PYTHON tools, PAReTT, to incorporate phylogenetic and molecular clock data into ecological and evolutionary reviews, and ABCal, to address potential biases in systematic reviews in evolution and ecology. The thesis concludes by highlighting the broader implications of the study, emphasizing the utility of biological clocks in understanding temporal traits, from annual life events in birds to lifelong aging in mammals. The generated datasets and tools contribute to ecological systematic reviews and individual studies, expanding our knowledge of biological clocks and guiding future research endeavours.
Thesis (Ph.D.(Genetics))--University of the Free State, 2024
Keywords: Molecular marker; Biological clocks; Circadian rhythms; Migration patterns in birds; Birds; Epigenetics; Aging in animals; Methylation; Telomere; Animals; Molecular biology; Biological rhythms; Aging - Molecular aspects; Cheetah - Age determination; Population monitoring